2009
DOI: 10.4314/wajae.v8i1.45801
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and macrobenthic invertebrate fauna characteristics of swampy water bodies within University of Lagos, Nigeria

Abstract: A comparative study conducted on three swampy water bodies draining through the University of Lagos into the Lagos Lagoon describes the physical, chemical and macrobenthic invertebrate characteristics of these water bodies at the study sites. Three stations, one at each water body were sampled fortnightly from June to December, 2000. Water temperature, total alkalinity and salinity were the only physical and chemical conditions significantly different at the study stations. The physical and chemical conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The chemistry of aquatic environment generally depends on the physical and geological features of the environment and some of the parameters evaluated in this study is to ascertain that the physical and chemical parameters estimated were within the range of those reported for similar brackish water [22,23,24,25] in Nigeria. Conductivity and total dissolved solids fluctuated during the wet and dry months and the elevated values of these parameters in the months of the dry periods are said to be due to evaporation while the low levels of these parameters observed in the wet months are a reflection of dilution by rainfall As indicated by the CCA ordination, the environmental variables are correlated with significant part of the variations in the individual species abundance.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The chemistry of aquatic environment generally depends on the physical and geological features of the environment and some of the parameters evaluated in this study is to ascertain that the physical and chemical parameters estimated were within the range of those reported for similar brackish water [22,23,24,25] in Nigeria. Conductivity and total dissolved solids fluctuated during the wet and dry months and the elevated values of these parameters in the months of the dry periods are said to be due to evaporation while the low levels of these parameters observed in the wet months are a reflection of dilution by rainfall As indicated by the CCA ordination, the environmental variables are correlated with significant part of the variations in the individual species abundance.…”
Section: Discussionmentioning
confidence: 89%
“…Over-time the benthic invertebrates become dominated by resilient communities that can tolerate stressful environmental conditions in the bottom sediment [1]. Once established, these resilient communities usually alter their environment through physical sediment alteration, enhancing sediment-water fluxes, increasing available area for solute exchange by reworking and bioturbation [6][7][8][9] in addition to promoting community succession, species settlement and populations persistence [10][11][12]9,1].…”
Section: Introductionmentioning
confidence: 99%
“…The study locations showed limited concentrations of phosphates as compared with that of nitrates. The increase in nutrients of the study sites can be attributed to the increase in anthropogenic activities (Edokpayi and Ayorinde, 2009;Edokpayi et al, 2010). Sept.…”
Section: Octmentioning
confidence: 95%
“…Ogbe creek is non tidal and experience flooding in the wet season as a result of surface runoff (Nwankwo and Akinsoji, 1992). The stream channel width is about 30 m with an average flow velocity of 0.5 cmS -1 (Edokpayi and Ayorinde, 2009). The station has a coordinate of 3°23.527'E and 6°30.627'N.…”
Section: Description Of Study Sitesmentioning
confidence: 99%
“…Lagos' population is currently about 17 million, up from 2 to 3 million in the 1970s. Despite this pressure, research to date on the lagoon only identifies ecological studies [17][18][19], lagoon sensitivity and pollution studies [17,20,21], fishery and plankton sustainability [22,23] and partial pressures on the lagoon ecosystem habitat. All these, although, are part of the outcome of the impact created by the growing population (about 17 million) of the city of Lagos Nigeria around the Lagos Lagoon.…”
Section: Rationale For the Researchmentioning
confidence: 99%